Bacterial Coaggregation in Bacteria Isolated from Dental Unit Waterlines - Si Young Lee; Hye Young Yoon (치위생과학회지)
Background: To understand the process of biofilm formation in dental unit waterlines (DUWLs), it is necessary to assess the of bacteria that constitute DUWL biofilms. This study assessed the coaggregation of bacterial species isolated from DUWL biofilms and other related mechanisms. Methods: Coaggregation was macroscopically evaluated. Cultures of the DUWLs isolates were adjusted to the same concentration (optical density [OD]600=1.5). The isolates were mixed in pairs and incubated for 1 hour at room temperature. Subsequently, the coaggregation values were scored. Some coaggregation pairs were observed through fluorescence microscope after staining with SYTOⓇ 9 and propidium iodide. To assess their coaggregation properties, inhibition of coaggregation was performed by adding sugars and amino acids to the coaggregation pairs and the coaggregation values were scored again post-addition. Results: Coaggregation was observed in 360 out of 406 coaggregation pairs, whose coaggregation scores of ranged from one to three points. Five pairs (1.4%) had a coaggregation score of 3 points. Among these five pairs, mannose most frequently inhibited coaggregation. Among the isolates, Cupriavidus pauculus HY12 and Beijerinckia derxii subsp. venezuelae HY7 had the highest number of coaggregation pairs, with scores of 2 and 3. Conclusion: Cupriavidus pauculus HY12 and B. derxii subsp. venezuelae HY7 form many coaggregation pairs and may play important roles in biofilm maturation. The results of this study can be used to propose methods to inhibit the formation of DUWL biofilms by inhibiting coaggregation.